Kata Dapat Merugikan Keuangan Negara Dalam Undang-Undang Tindak Pidana Korupsi dan Undang-Undang Perbendaharaan Negara - Salmon, Harly Clifford Jonas (Pusat Kajian Korupsi Fakultas Hukum Universitas Pattimura, 2023)
Introduction: The element of State Financial Loss in the Corruption Law as a formal offence where to prove the state financial loss whether the state lost or not, is not important but more emphasis on the potential financial loss of the state and the State Treasury Law as a material offence which emphasizes that the state financial loss must be proven and calculated. Purposes of the Research: Analysing the Elements of State Financial Loss in the Corruption Law and the State Treasury Law. Methods of the Research: The research method used is normative juridical, with a statutory and conceptual approach. The sources of legal materials used are primary, secondary, and tertiary legal materials. The technique of collecting legal materials carried out in this research is through literature study, namely by searching legal materials by reading, seeing, listening, or now it is mainly done by searching via the internet. The data will be analyzed using quantitative data analysis techniques in a quantitative approach. Quantitative related to the relationship of variables is analyzed using an objective theory, then described to solve the main problem in this study. Results of the Research: the conclusions can be drawn as follows: The element